Fiscal policies, public investments and wellbeing: mapping the evolution of the EU - Massimiliano Mazzanti; Matteo Mazzarano; Andrea Pronti; Marco Quatrosi (Insights into Regional Development)
The European Union faced several crises in the last twenty years that destabilized its macroeconomic equilibrium and development capacity. Standard economic methodologies were capable of neither predicting nor completely solving these crises through appropriate investments. To understand the overall development performance, the well-known Human Development Index (HDI) is the most widely deployed conceptual framework. In this article, we look at the components of welfare dynamics in the EU by examining socio-economic performance. Through a ‘beyond gross domestic product (GDP)’ approach, we analyse public expenditures, especially focusing on the pillars of growth and socio-economic development: education, health, and total R&D. We believe that convergence policies and sustainability policies should together be given a greater role within the EU agenda. They are necessarily interlinked with each other and with the common welfare, the true objective of public policy. European strategies on the key human development pillars were heterogeneous during the last decades. The post 2009 recession was characterized by non-expansionary measures that have undermined development in most countries. Due to the lack of a robust investment patterns towards human and sustainable development, European countries were not fully prepared to tackle the COVID-19 shock. Growth and development figures were already gloomy in 2019 and the years before. The hope is that this lesson is useful to create a solid society and economic system for possible future crises.